Penggunaan Perangkat Lunak Dalam Pengelolaan Arsip Konvensional Dan Elektronik - Habiburrahman Habiburrahman (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2016)
Archival is something that can not be separated from an organization or institution, archival has such an important role, it can be considered when making a decission or be a concrete evidence. In its development, the archive keep following techonological changes, now archives are not only the shape of an object but also something that stored digitally known as electronic archives. Record managemet is an effort done by archival association to provide service in accordance with the character of today’s society, through this article the writer wants to convey about the management of both digital and conventional archives as well as the software that became modern media in archival management in order to facilitate the task and archival services.